Problematika pomorskog povezivanja zadarskih otoka sa Zadrom - STRGAČIĆ, Ivan; PEŠUŠIĆ, Ante (Promet - Traffic&Transportation, 2026)
ISSUES OF PROVISION OF LINEAR SERVICES BETWEEN THE ZADAR ISLAND GROUP AND ZADAR The authors review the current status of shipping services between the city of Zadar and the island group of Central Dalmatia and reiterate the unsatisfactory condition of vessels operating in the region. The authors highlight individual examples of lines operating past the limits of capacity and suggest possible improvements.